Oracle9i: The Complete Reference - Loney, Kevin (McGraw-Hill, 2011)
Master all the powerful features of Oracle9i using the exclusive information inside this indispensable resource. Written by best-selling Oracle Press authors Kevin Loney and George Koch, this volume explains how to implement all the components of Oracle9i. This is a must-have reference for all Oracle professionals.